A novel splice-site mutation in the ASPM gene underlies autosomal recessive primary microcephaly - Hashmi, Jamil A. (Ann Saudi Med, 2016)
BACKGROUND: Autosomal recessive primary microcephaly (MCPH) is a clinically and genetically heterogeneous disorder. Patients with MCPH exhibit reduced occipito-frontal head circumference and non-progressive intellectual disability. To date, 17 genes have been known as an underlying cause of MCPH in humans. ASPM (abnormal spindle-like, microcephaly associated) is the most commonly mutated MCPH gene. OBJECTIVE: Identify the genetic defect underlying MCPH in a Saudi family. DESIGN: A cross-sectional clinical genetic study of a Saudi family. SETTING: Madinah Maternity and Children Hospital and Centre for Genetics and Inherited Diseases, Taibah University. PATIENTS AND METHODS: A molecular analysis was carried out on DNA samples from 10 individuals of a Saudi family segregating MCPH. DNA was isolated from the peripheral blood of 10 individuals, including 2 patients, and whole exome sequencing was performed using the Nextera Rapid Capture kit and NextSeq500 instrument. VariantStudio was used to filter and prioritize variants. MAIN OUTCOME MEASURE(S): Detection of mutation in the ASPM gene in a family segregating autosomal recessive primary microcephaly. RESULTS: A novel homozygous splice-site variant (c.3742-1G>C) in the ASPM gene was identified. The variant is predicted to have an effect on splicing. Human Splice Finder, an in silico tool, predicted skipping of exon 16 due to this variant. CONCLUSION: Skipping of exon 16 may change the order and number of IQ motifs in the ASPM protein leading to typical MCPH phenotype. LIMITATIONS: Single family study.